How companies can capture and retain generation Z talent: The influence of employer branding dimensions on talent management - Batalha, Carolina Maria Roussado (2023)
The labor market is constantly changing, not only because it has gone through a pandemic period that has given rise to different ways of working, but also because it now embraces a new generation with different perspectives, needs, and ambitions - Generation Z. The traditional organizational model is no longer adequate to meet the expectations of this generation, and for companies to be able to compete in the current war for talent, they need to keep up with market trends. Unlike previous generations, who put salary and career advancement as a priority, this generation tends not to want to replicate this lifestyle. Based on a quantitative approach through questionnaire data collection, the study investigates the characteristics of Generation Z, what these professionals look for in a job offer, and what motivates them to stay with an organization. In addition, it analyzes the influence of employer branding dimensions on talent attraction and retention, identifying the most valued dimensions in this process. The results of this research provide a significant contribution for companies interested in attracting and retaining Generation Z talent. Understanding the specific preferences and needs of this generation, allows organizations to adapt their talent management strategies, becoming more attractive and competitive in the current labor market. This study contributes to the existing literature, as there is still a knowledge gap in managing Generation Z talent.